Inducible Nitric Oxide Synthase/Nitric Oxide System as a Biomarker for Stress and Ease Response in Fish: Implication on Na+ Homeostasis During Hypoxia - Peter, M. C. Subhash; Gayathry, R.; Peter, Valsa S. (Frontiers in Physiology, 2022)
The cellular and organismal response to stressor-driven stimuli evokes stress response in vertebrates including fishes. Despite showing a varied pattern of stress response including ion-osmotic stress response, fishes have also developed mechanisms to show ease or recovery response that attenuate the magnitude of stress response with the aid of certain neuroendocrine signals. Among these signaling factors, nitric oxide (NO) as an autocrine/paracrine signaling molecule that controls many physiological processes, exerts a role in attenuating the impact of stress response particularly during hypoxia stress in fishes. The present review thus focuses on the role of NO in the regulation of ion homeostasis during stress and ease response in fish as limited information is available on this very important aspect of ion transport physiology that contributes to the mechanism of survival during environmental challenges. Isoforms of nitric oxide synthase (NOS) that are involved in the synthesis and availability of NO at the cellular level makes NOS/NO system a unique molecular drive which shows both regulatory and integrative mechanisms of control. Modulation of NOS/NO system particularly inducible NOS (iNOS)/NO has been linked with cellular and systemic Na+ homeostasis in stressed fish. The higher sensitivity of iNOS to varied physical stressors in fishes further document a critical role for iNOS/NO system in the regulation of Na+ homeostasis, pointing to its signature role as biomarker for stress and ease response in fish.